Fabrication of SOFC Using BaZr0.8Y0.2O3-δ Nano-Slurry Electrolyte. (10th July 2019) - Nakamura, Moe; Sakai, Takaaki; Kato, Toru; Koura, Setsuko; Oohira, Akihiro
Abstract : Lowering the sintering temperature of the BaZr0.8 Y0.2 O3-δ (BZY) by grinding BZY powder to nano-size particles was studied. BZY nano-slurry was fabricated by a planetary ball-mill. Obtained nano-slurry was coated on a NiO / BZY anode substrate by a spin-coater and sintered at the temperature of 800 to 1000 ℃. Crystal structure and composition of the fabricated electrolyte layer were measured by an X-ray diffractometer (XRD) and an energy dispersive X-ray analyzer (EDX), respectively. Further, morphology of the coating layer was observed by a scanning electron microscope (SEM). As a result, dense transparent layers were obtained by sintering at temperature more than 800 ℃. Thickness of the layers is about 1 μm. The crystal structure and composition of the layers was consistent with that of the raw BZY powder. Therefore, dense thin BZY layers were fabricated on the NiO / BZY anode substrate successfully.